Self-Reflection and Transformation Among Ningxia International Students in Malaysia - Zhang, Rui; Abdul Wahab, Norwaliza; Dawi, Amir Hasan; Hashim, Abdul Talib Mohamed; Mansor, Rosnidar (International Journal of Educational Management and Development Studies, 2022)
The study investigated the learning experiences and the adaptation process among Ningxia China international students studying in Malaysia. The paper aims to highlight the researcher’s self-reflection on the learning experience which led to self-transformation. The study employed a qualitative paradigm where a total of the ten participants were interviewed. Through a unique self-reflection during analysis, the researcher placed herself in the study and supported by ten other respondents. The researcher went through a rigorous search within herself. In addition, a set of semi-structured questions was used during the interview. The self-reflection of the researcher was conceptualized, interviews were transcribed and data were triangulated. Coding and constant comparison were adopted during data analysis. The findings showed the sub-themes of the learning experiences which led to self -transformation. The results yielded from this study contributed significantly towards the notion of transformation, study abroad and internationalisation. Thus, this implies that to able to succeed while studying abroad, it is important to understand the learning processes and the outcomes of the transformation within an individual.